2012
DOI: 10.1371/journal.pone.0031286
|View full text |Cite
|
Sign up to set email alerts
|

Caffeic Acid Phenethyl Ester Causes p21Cip1 Induction, Akt Signaling Reduction, and Growth Inhibition in PC-3 Human Prostate Cancer Cells

Abstract: Caffeic acid phenethyl ester (CAPE) treatment suppressed proliferation, colony formation, and cell cycle progression in PC-3 human prostate cancer cells. CAPE decreased protein expression of cyclin D1, cyclin E, SKP2, c-Myc, Akt1, Akt2, Akt3, total Akt, mTOR, Bcl-2, Rb, as well as phosphorylation of Rb, ERK1/2, Akt, mTOR, GSK3α, GSK3β, PDK1; but increased protein expression of KLF6 and p21Cip1. Microarray analysis indicated that pathways involved in cellular movement, cell death, proliferation, and cell cycle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
72
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(79 citation statements)
references
References 65 publications
(74 reference statements)
6
72
1
Order By: Relevance
“…Their cytoprotective activities were much better than those of the parent compound CAPE under the same concentrations. Compounds 3, 4, 12, 13, 15, 16 and 19 showed similar protective capabilities to CAPE within the range of 62.9−81.1% at 4 nM, while compounds 1−4, 6,7,9,10,12,13,16,19, and 20 possessed equivalent protective effects as CAPE within the range 61.9−93.9% at 40 nM (Figure 1). Other CAPE derivatives demonstrated poorer activities against H 2 O 2 -indued cytotoxicity (data not shown).…”
Section: Scheme 1 Synthesis Of Cape Derivatives Amentioning
confidence: 95%
“…Their cytoprotective activities were much better than those of the parent compound CAPE under the same concentrations. Compounds 3, 4, 12, 13, 15, 16 and 19 showed similar protective capabilities to CAPE within the range of 62.9−81.1% at 4 nM, while compounds 1−4, 6,7,9,10,12,13,16,19, and 20 possessed equivalent protective effects as CAPE within the range 61.9−93.9% at 40 nM (Figure 1). Other CAPE derivatives demonstrated poorer activities against H 2 O 2 -indued cytotoxicity (data not shown).…”
Section: Scheme 1 Synthesis Of Cape Derivatives Amentioning
confidence: 95%
“…CAPE is a well known NF-κB inhibitor at concentrations of 50 μM to 80 μM by preventing the translocation of p65 unit of NF-κB and the binding between NF-κB and DNA [17]. We previously reported that CAPE dosage dependently suppressed the proliferation of androgen-dependent LNCaP 104-S and AR-negative PC-3 cells [18, 19]. Administration of CAPE by gavage significantly inhibited the tumor growth of LNCaP and PC-3 xenografts in nude mice [1820].…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that CAPE dosage dependently suppressed the proliferation of androgen-dependent LNCaP 104-S and AR-negative PC-3 cells [18, 19]. Administration of CAPE by gavage significantly inhibited the tumor growth of LNCaP and PC-3 xenografts in nude mice [1820]. We discovered that CAPE treatment inhibited cell growth and induced G1 cell cycle arrest by suppressing c-Myc and Akt-related protein signaling networks in LNCaP 104-S and PC-3 cells [1820].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Androgen ablation therapy is an effective treatment during the early stages of PCa; however, it is associated with several side effects including loss of libido and bone density as well as cardiovascular morbidity [2]. Moreover, most PCa ultimately progresses to metastatic castration-resistant PCa (CRPC) after hormone therapy [3,4,5]. Although clinical trial data have shown that enzalutamide and abiraterone acetate significantly prolong overall survival in patients with metastatic CRPC, there is currently no systemic and effective therapy for CRPC [5,6,7].…”
Section: Introductionmentioning
confidence: 99%